(3fXe aj JGQjN GdOhdI GdehQjJGfjI GddeJhfjIs - (3eMeO eNJGQ Hf eMeO GdjYbhHjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3hHYO agPG fXe ddJGQjN GdOhdI GdehQjJGfjI GdeSdeI hMjGI HYV edhcgG GdChdjf hVYg GdabjQ Zdi QHg eMeO eNJGQ Hf eMeO Hf YHO Gddg Hf Ye GdjYbhHi fSHkG s
(3BNQgG (B:s
(3jfJgi HGdMOjK Yf GHf JGTajf Hbhdg (B: (3hYGT bQfkG cGedkG hGSJTgO HeZQH ceG GJi ebjOkG hbHd Cf jehJ cGf YgOG dfLdg GdYdi Ydi HGdgOi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI MOjKI YfGhjf aUhdgG HGdMHQ GdCShO s
(3hYdi ghGeTgG HYV GdTQhM hGdJUhjHGJ s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs